ANÁLISE DO PROCESSO DE GESTÃO DE COMPRAS: UM ESTUDO DE CASO EM UMA CONSTRUTORA EM LINHARES/ES. (REMUNOM, 2024)
The purchasing management process in the organization is of supreme importance, as it contains a series of activities that are crucial for the efficient functioning of the company, playing an integral role in the cost reduction strategy in the construction sector. Furthermore, the interconnection between the purchasing process and production is worth highlighting, as decisions to acquire materials and inputs directly affect the production capacity and timeline of construction projects. Therefore, the objective of this article addresses the acquisition of materials from a construction company in the region of Linhares, Espírito Santo, aiming to identify what has been advantageous for the company and what can be improved through viable purchasing management solutions. To support this analysis, the research adopted a bibliographic methodology and a qualitative approach, using direct observation as the main research technique, which involved visits to the construction company, analysis of relevant documents and detailed interviews with the manager and buyer responsible.